Environmental impacts of the generating station of electricity in the baadare district - Khaleel, Zhiyan (Humanities Journal of University of Zakho, 2024)
Electrical stations have a significant impact and damage on the environment depending on the method of electricity generation. Typically, the raw materials such as coal, fuel, and crude or black oil are used in the electricity production. However, the critical issue arises from the combustion of these materials in which they produce gases that contain toxic materials such as carbon-monoxide, carbon dioxide and sulfur dioxide, ...etc. Based on this, the Baadre Electrical Station, which relies on black oil to generate electricity, was studied to demonstrate the extent of its impact on the surrounding environment. It became evident that this electrical station negatively affects the surrounding areas through two main types of pollutants; air pollution and noise pollution. It has been demonstrated that the Baadre Electrical Station plays a role in polluting the local environment due to the station’s proximity to the residential areas. This proximity leads to environmental damage that directly effects on humans. This damage arises from the gases emitted from the station, large noise, as well as the vibrations in residential areas.